Proper balance between teacher talking time (TTT) and student talking time (STT) in EFL classroom context - Aurin, Ibthesham (BRAC University, 2018)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2017.